Pangiling-Iling Jagat Nusa Penida: Analisis Semiotik - Paramasuta Wijaya, Made; Wijana, I Made; Suarka, I Nyoman (Humanis, 2016)
In regard the title is pangiling-iling meaningful reminder-recall, showed no point in the text Pangiling-iling Jagat Nusa Penida to be conveyed to always be remembered by the people. It is interesting to study. The research team Balai Bahasa Bali Province in the study " Pemetaan Sastra Bali 2014 " describes this text as a myth. On this occasion, Pangiling-iling Jagat Nusa Penida studied again in more depth, aims to study the structure and meaning of the text, using the structural theory and semiotics. The results of this study are Pangiling-iling Jagat Nusa Penida is expressed as a literary history, because it contains elements of literary history, not just an element of myth as described in the earlier study. It is an advantage of this study. In addition to containing elements of history, Pangiling-iling Jagat Nusa Penida containing fictional elements as one of the builders of the structure of literary works. Structure Pangiling-iling Jagat Nusa Penida includes the mandate, theme, character and characterization, incident and plot, setting, and fictitious elements literary history including mythology, legend, hagiography, symbolism, and suggestion. While the meaning of Pangiling-iling Jagat Nusa Penida is the harmony of the universe Bali-Nusa, covering the harmonious relationship between man and God, the harmony of human relations, and the harmony of human relationships with the natural environment.